1993
DOI: 10.2307/1243980
|View full text |Cite
|
Sign up to set email alerts
|

Insurance, Moral Hazard, and Chemical Use in Agriculture

Abstract: This paper examines how crop insurance affects corn farmers' fertilizer and pesticide use in the U.S. Midwest. Crop insurance might be expected to affect chemical use because of “moral hazard”; insured farmers may undertake riskier production than do uninsured farmers. Results suggest that insurance exerts considerable influence on corn farmers' chemical use decisions. Those purchasing insurance applied significantly more nitrogen per acre (19%), spent more on pesticides (21%), and treated more acreage with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
175
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(194 citation statements)
references
References 14 publications
10
175
0
Order By: Relevance
“…There is extensive literature on the potential environmental impacts of government-sponsored risk management programmes such as subsidised crop insurance and crop disaster payments (Horowitz and Lichtenberg 1993, Smith and Goodwin 1996, Wu 1999, Seo, Mitchell and Leatham, 2005 Concerning the use of chemical input, early studies examined the impact of price uncertainty on a competitive, one-input, one-output firm (Sandmo, 1971;Ishii, 1977;Briys and Eeckhoudt, 1985;Hey, 1985). Pope and Kramer (1979) modelled production risks by analyzing their effects on input use.…”
Section: Risk Management and Environmental Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is extensive literature on the potential environmental impacts of government-sponsored risk management programmes such as subsidised crop insurance and crop disaster payments (Horowitz and Lichtenberg 1993, Smith and Goodwin 1996, Wu 1999, Seo, Mitchell and Leatham, 2005 Concerning the use of chemical input, early studies examined the impact of price uncertainty on a competitive, one-input, one-output firm (Sandmo, 1971;Ishii, 1977;Briys and Eeckhoudt, 1985;Hey, 1985). Pope and Kramer (1979) modelled production risks by analyzing their effects on input use.…”
Section: Risk Management and Environmental Policiesmentioning
confidence: 99%
“…One of the most cited contributions is the research by Horowitz and Lichtenberg (1993). They showed that in many instances pesticides are more accurately viewed as risk-increasing.…”
Section: Risk Management and Environmental Policiesmentioning
confidence: 99%
“…However, conventional agricultural insurance with a single rate has some well-known problems, including adverse selection (Quiggin et al 1993;Just et al 1999;Makki and Somwaru 2001), moral hazard (Horowitz and Lichtenberg 1993;Smith and Goodwin 1996), and systemic risk (Miranda and Glauber 1997;Miranda and Farrin 2012). Given these problems associated with conventional agricultural insurance, in the past two decades a growing number of national governments, academic researchers, and international nongovernmental organizations have exhibited great interest in a new form of agricultural insurance known as weather index insurance, which is based on recorded meteorological data that are highly associated with crop losses (Barnett and Mahul 2007;Bryla and Syroka 2007;Chantarat et al 2007;Miranda and Farrin 2012;Cao et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases of interest, however, the client has the capacity to take action that will affect the occurrence and magnitude of gains and losses. This arises most obviously in the case of agricultural insurance, where the loss to be insured is a loss of production because of climatic shocks or insect infestation, and clients may undertake such actions as the application of fertiliser and pesticides (Miranda, 1991;Horowitz and Lichtenberg, 1993;Chambers and Quiggin, 1996). However, the same issues arise whenever clients have the capacity to undertake self-insurance or self-protection (Ehrlich and Becker, 1972;Lewis and Nickerson, 1989;Quiggin, 2002).…”
Section: Introductionmentioning
confidence: 99%